Improving Bilingual Service Delivery in Catholic Schools through Two-Way Immersion - Scanlan, Martin; Zehrbach, Gareth (Catholic Education: A Journal of Inquiry and Practice, 2010)
Catholic elementary schools underserve Latino students, especially those who are bilingual. This paper presents a conceptual argument for Catholic elementary schools to improve this by pursuing the two-way immersion model of bilingual service delivery in Spanish and English. The argument is presented in three stages. First, we show that Catholic elementary schools underserve Latino families in general, and bilingual Latino students with limited profi ciency in English in particular. Next, we present evidence from research literature and a case study that the two-way immersion approach to bilingual service delivery is philosophically and functionally well suited for Catholic schooling. We conclude by suggesting the implications of this argument for Catholic as well as other private sector schools.